2004
DOI: 10.1152/ajpcell.00465.2003
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of PKC-dependent and -independent processes in temporal ERK regulation by ET-1, PDGF, and EGF in rat myometrial cells

Abstract: Endothelin-1 (ET-1), platelet-derived growth factor (PDGF), and epidermal growth factor (EGF) stimulated thymidine incorporation with different efficiency (PDGF >> EGF = ET-1) in rat myometrial cells. They also stimulated ERK activation, which culminated at 5 min and then declined to reach a plateau (at 45 min: EGF > 90%, PDGF = 50%, and ET-1 < 10% of maximum). Inhibition and downregulation of PKC demonstrated that ERK activation at 5 min involved PKC delta and -zeta for ET-1 and PKC alpha plus another PKC iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 46 publications
1
29
3
1
Order By: Relevance
“…In conclusion, our data support a model whereby PDGF pathway signaling via MEK 3369 RESEARCH ARTICLE PDGF signaling promotes expansion of ExEn and PKC plays a key role in XEN cell propagation. However, the exact and respective roles of MEK and PKC remain unclear, and we cannot exclude cross-talk, as has been reported in various cell systems (Lee et al, 2006;Okazaki et al, 2000;Robin et al, 2004). Future studies will be required to address the specific and combinatorial roles of these signal transducers.…”
Section: Discussionmentioning
confidence: 93%
“…In conclusion, our data support a model whereby PDGF pathway signaling via MEK 3369 RESEARCH ARTICLE PDGF signaling promotes expansion of ExEn and PKC plays a key role in XEN cell propagation. However, the exact and respective roles of MEK and PKC remain unclear, and we cannot exclude cross-talk, as has been reported in various cell systems (Lee et al, 2006;Okazaki et al, 2000;Robin et al, 2004). Future studies will be required to address the specific and combinatorial roles of these signal transducers.…”
Section: Discussionmentioning
confidence: 93%
“…Clerk et al 2006 found that EGF increases cardiomyocyte Ras.GTP and activates c-Raf and ERK1/2 phosphorylation independently of PKC. Similarly, there is evidence that EGF activation of ERK1/2 in non-cardiac muscle is PKC-independent and Ras-dependent (Robin et al, 2004). These findings suggest that direct ligation of the EGFR removes the PKC dependence of signalling, implicating upstream functions of the kinase in regulating ligand levels and EGFR phosphorylation.…”
Section: Pkcmentioning
confidence: 86%
“…EGF also activates the PI-3 kinase/Akt pathway in other tissues, synergizing with PLCγ activity in mediating EGF effects [27]. EGF activation of ERK in myometrium is PKC-independent and involves the conventional Ras pathway [28]. EGF has also been implicated in myometrial cell proliferation in a pathway involving PKC and eicosanoids [29].…”
Section: Contractant and Relaxant Signaling Pathways Stimulate Multipmentioning
confidence: 99%